Numerical model to calculate bed changes in multiple connected river channels - Nemer, Nemer; López, José Luis (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The numerical simulation of flow and sediment movement in multiple connected networks of channels is not simple due to the interaction between flow hydraulics and sediment transport that occur in the different branches. In this paper, a numerical model is proposed to estimate the bed variations in braided rivers, using the most recent and complete equations to predict the friction and sediment transport in alluvial rivers. The model is based on the numerical solution to the Saint Venant equations applied to a river composed of multiple islands. The validation of the model is made by analyzing a simplified case of flow around a single island, and by comparison with observed data in the Apure River system.